W poszukiwaniu początków oraz prób zrozumienia „zachowań symbolicznych”. Zarys problematyki - Józefów-Czerwińska, Bożena (Folia Praehistorica Posnaniensia, 2020)
In academic literature there is a whole range of hypotheses relating to the genesis of the symbolic behavior, which are usually also associated with the beginnings of the development of spirituality. In the nineteenth century, the considerations conducted in this area were often influenced by negative stereotypes (relating, among others, to hunter-gatherers), which were later deconstructed. Although the discussion on this subject has been ongoing since the nineteenth century, even in the light of research and achievements of the modern science, the problem of the origins of symbolic behavior has still not been unequivocally resolved. However, it is assumed that they should be attributed primarily to the changes that were initiated in our ancestors from the Homo Sapiens family. In recent years, however, some ethologists and primatologists believe that the genesis of symbolic behavior should be sought in the animal world. I devote my article to this diversified subject matter.